Physical and physiological profile of professional female handball players - Renouf, F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Physical profile of professional female handball (HB) team can help coaches and physical trainer to adapt and individualize physical training. Profile knowledges allow to know which fitness qualities are required for a high level of practice. Power, aerobic fitness, strength and an optimal body composition are required in a goal of success in different competition (1,2). To our knowledges, no study in professional female HB has investigated physical and physiological collective and individual profile of players. Therefore, the purpose of this study was (i) to describe collective and individual profile of a professional female HB and (ii) to compare the front line (FL) players composed by wings and pivots, and the rear line (RL) players composed by backs.